Predictors to employees with disabilities’ organisational behaviour and involvement in employment - Wok, Saodah; Hashim, Junaidah (Emerald Group Publishing Limited, 2014)

(untitled)
Purpose – The purpose of this paper is to examine the work challenges of employees with disabilities and predict the organisational behaviours of employees and their involvement in employment. Design/methodology/approach – A self-developed questionnaire was used to gather relevant information from employers, employees with disabilities and their co-workers. The questionnaires were distributed and administered by a number of trained enumerators. Findings – Both employers and co-workers perceived that their organisations have provided conducive organisation climate, comfortable work environment and reasonable adjustment for their employees with disabilities. Employees with disabilities are found loyal and committed. They are satisfied with the job. Organisational loyalty and commitment are predicted by the organisations’ ability to restructure their job design to suit to the needs of employees with disabilities. Research limitations/implications – Initially, this study planned to use purposive sampling; however, due to poor database maintained by the relevant agency of employees with disability employment in the country, the paper was unable to identify which employers employ how many employees with disabilities. The sampling then was based on convenient sampling. Practical implications – Job design, organisational climate and comfortable work environment have long been recognised for motivating employees’ performance (Hackman et al., 1975; Garg and Rastogi, 2006). The paper’s findings show that these factors also motivate employees with disabilities. This is added value to the existing body of knowledge as limited is known about the motivation of employees with disabilities. Originality/value – This study is unique because it gathers data from several parties: employees with disabilities, the co-workers and the employers.